2021
DOI: 10.1007/s11240-021-02082-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a DREB 5-A subgroup transcription factor gene from Ricinus communis (RcDREB1) enhanced growth, drought tolerance and pollen viability in tobacco

Abstract: Climate change has increased the frequency of long periods of drought, affecting crop cultivation worldwide. Losses due to water stress exceed ten percent of world production of major crops, reaching three-quarters of production areas, with severe economic losses. Therefore, the generation of environmental stress-tolerant genotypes that are more e cient in water use is extremely important. We have previously isolated and characterized a DREB transcription factor coding gene, named RcDREB1, from castor bean (Ri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…DREBs regulate stress-defensive genes expression by binding to the DRE/C-repeat core component of these downstream genes under different abiotic stresses [ 44 ]. It has been found that transgenic tobacco overexpressing an RcDREB 5-A showed better growth and higher biomass than non-transgenic lines in response to drought stress [ 45 ]. Similarly, up-regulation of PcDREB2A could significantly improve drought tolerance of Arabidopsis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…DREBs regulate stress-defensive genes expression by binding to the DRE/C-repeat core component of these downstream genes under different abiotic stresses [ 44 ]. It has been found that transgenic tobacco overexpressing an RcDREB 5-A showed better growth and higher biomass than non-transgenic lines in response to drought stress [ 45 ]. Similarly, up-regulation of PcDREB2A could significantly improve drought tolerance of Arabidopsis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the functions of the A-1 and A-2 subgroups have been extensively explored [ 14 ], the roles and underlying mechanisms of A-5-type DREB genes have garnered limited attention and remain relatively enigmatic, despite their promising potential. In recent years, of the majority of studies have reported that A-5 DREB transcription factors can significantly enhance stress tolerance in plants [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Collectively, these investigations highlighted the potential of A-5 DREB genes as promising candidates for crop breeding programs aimed at enhancing stress tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…A little was reported on photosynthetic traits in castor. Previous studies have reported that photosynthetic O 2 -evolution and 14 CO 2 -fixation rates in blades decreased with increasing nuclear genome duplication 25 ; Photosynthesis in capsule wall promotes fuller seed filling 26 , and that in seed coat increases lipid accumulation 27 , seedling growth 28 and seed development 29 ; In response to stresses such as high temperature, drought, flooding and high salinity, castor plants reduce water loss by decreasing stomatal conductance to prevent irreversible leaf wilting and further develop mechanisms to adapt to the environment 30 34 ; RcDREB1 , a pollen-specific and desiccation-associated transcription factor gene from castor, enhanced the drought tolerance (lower Tr), photosynthetic rate, biomass and pollen grain viability of transgenic tobacco 35 . The information concerning the genetic mechanism of photosynthetic traits is a serious shortage in castor.…”
Section: Introductionmentioning
confidence: 99%